The Effectiveness of Education Models to Increase Exclusive Breastfeeding Practices: A Scoping Review - Murti Ani; Zahroh Shaluhiyah; Anggorowati Anggorowati; Siti Khuzaiyah (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Experts recommend exclusive breastfeeding for the first six months of life to achieve optimal growth and health. However, this practice has not yet become widespread, and global growth rates remain relatively low. Various educational breastfeeding models have been widely implemented to help mothers succeed in exclusive breastfeeding. This study aims to explore and summarize the evidence for effective education models to increase exclusive breastfeeding.Method: A comprehensive search was conducted across three databases (PubMed, ScienceDirect, and Scopus). The PRISMA guidelines were used to select 20 peer-reviewed studies published between January 2016 and December 2025 that met the inclusion criteria. Data were extracted on education models, intervention objectives, and behavioral outcomes. Result: The results of the study showed that self-disclosure in MSM was influenced by Mothers need access to skilled, practical help and counseling support from trained health workers and counselors to implement optimal breastfeeding practices. A combination of antenatal and postnatal interventions, including home visits and media education such as flipcharts, booklets, videos, educational kits, telephone, SMS text messages, and WeChat support, can also increase exclusive breastfeeding at 6 months. The choice of breastfeeding education model influences the practice of exclusive breastfeeding. Therefore, it is important to consider the available time, resources, and media to support mothers in providing exclusive breastfeeding and achieving their breastfeeding education goals.Keywords: Breastfeeding, Education, Effectiveness, Model